2021
DOI: 10.1037/per0000457
|View full text |Cite
|
Sign up to set email alerts
|

The “Big Everything”: Integrating and investigating dimensional models of psychopathology, personality, personality pathology, and cognitive functioning.

Abstract: Common factors are increasingly used to model the structure of psychopathology ("p"), personality (General Factor of Personality [GFP]), pathological personality (General Factor of Pathological Personality [GFPP]), and intelligence ("g"). Using 4 waves spanning ages 18 -29 in a cohort of college students (baseline n ϭ 489), this study used indicators of psychopathology, personality, pathological personality, and cognitive functioning to compare models that included Cognitive Functioning, p, GFP, GFPP, and a "B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 57 publications
(92 reference statements)
4
11
0
Order By: Relevance
“…Distress is then combined with other heterogeneous groupings (e.g., fear, eating pathology, mania, sexual problems) under the umbrella of “internalizing.” As one moves up the hierarchy, the scores become less and less useful. As noted by Littlefield and colleagues (2021), “currently, there is no clear consensus . .…”
Section: Claim 2 Hitop Will Solve the Problems Of Comorbidity And Het...mentioning
confidence: 99%
“…Distress is then combined with other heterogeneous groupings (e.g., fear, eating pathology, mania, sexual problems) under the umbrella of “internalizing.” As one moves up the hierarchy, the scores become less and less useful. As noted by Littlefield and colleagues (2021), “currently, there is no clear consensus . .…”
Section: Claim 2 Hitop Will Solve the Problems Of Comorbidity And Het...mentioning
confidence: 99%
“…Like previous studies, the cross-sectional associations between the GFP and the p factor in Study 1 (between r = .42, p <.001 and r = .47, p <.001) and in Study 2 (r = .52, p <.001 for T1 and r = .27, p <.001 for T2) are similar regardless of the extraction method employed to obtain the GFP (van der Linden et al, 2017). Beta indices are also similar in magnitude to the correlations reported by Rosenstrom et al (2019), and are somewhat lower than those reported by Oltmanns et al (2018) and Littlefield et al (2020). Overall, our results support that these general factors share a considerable amount of variance, and may reflect the extent of impairment or dysfunction in respective persons' lives, irrespectively of whether that impairment is attributed to psychopathological symptoms, personality disorders or a certain personality configuration (Oltmanns et al, 2018).…”
Section: Associations Between Personality and Psychopathologysupporting
confidence: 88%
“…This continuity-based perspective on psychopathology can be extended to associations between personality and psychopathology given, on the one hand, the structural similarities displayed by both personality and psychopathology (Krueger et al, 2020;Widiger et al 2018) and the high covariation between general factors of personality and psychopathology (Littlefield et al, 2020;Oltmans et al, 2018) observed throughout this thesis. Consequently, it is noticed that the normative personality variation and maladaptive dispositions related to psychopathology appear to be organized as domains that can be well-conceptualized as maladaptive extensions of FFM domains .…”
Section: Associations Between Personality and Psychopathologymentioning
confidence: 87%
“…In fact, because psychopathology reflects undesirable and dysfunctional behavior and experience, psychopathology ratings may be even more prone to evaluative consistency bias. Second, researchers have simultaneously modeled general factors of personality and psychopathology in adults and found that they are highly correlated (Littlefield et al, 2021;Oltmanns et al, 2018).…”
Section: P-factor and Multitrait-multimethods Modelingmentioning
confidence: 99%